MHC II-PI3K/Akt/mTOR Signaling Pathway Regulates Intestinal Immune Response Induced by Soy Glycinin in Hybrid Grouper: Protective Effects of Sodium Butyrate - Yin, Bin; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Chi, Shuyan; Yang, Qihui; Zhang, Shuang (Frontiers in Immunology, 2021)
Soy glycinin (11S) is involved in immune regulation. As an additive, sodium butyrate (SB) can relieve inflammation caused by 11S. To further delve into the mechanisms. A diet containing 50% fishmeal was the control group (FM group), and the experimental groups consisted of the FM group baseline plus 2% glycinin (GL group), 8% glycinin (GH group), and 8% glycinin + 0.13% sodium butyrate (GH-SB group). The specific growth ratio (SGR), feed utilization, and density of distal intestinal (DI) type II mucous cells were increased in the GL group. In the serum, IFN-γ was significantly upregulated in the GL group, and IgG and IL-1β were upregulated in the GH group. IgG, IL-1β, and TNF-α in the GH-SB group were significantly downregulated compared to those in the GH group. The mRNA levels of mTOR C1, mTOR C2, and Deptor were upregulated in the GL, GH, and GH-SB groups in the DI compared with those in the FM group, while the mRNA levels of mTOR C1 and Deptor in the GH group were higher than those in the GL and GH-SB groups. 4E-BP1, RICTOR, PRR5, MHC II, and CD4 were upregulated in the GH group. TSC1, mLST8, and NFY mRNA levels in the GL and GH-SB groups were upregulated compared with those in the FM and GH groups. Western blotting showed P-PI3KSer294/T-PI3K, P-AktSer473/T-Akt, and P-mTORSer2448/T-mTOR were upregulated in the GH group. Collectively, our results demonstrate that low-dose 11S could improve serum immune by secreting IFN-γ. The overexpression of IgG and IL-1β is the reason that high-dose 11S reduces serum immune function, and supplementing SB can suppress this overexpression. Low-dose 11S can block the relationship between PI3K and mTOR C2. It can also inhibit the expression of 4E-BP1 through mTOR C1. High-dose 11S upregulates 4E-BP2 through mTOR C1, aggravating intestinal inflammation. SB could relieve inflammation by blocking PI3K/mTOR C2 and inhibiting 4E-BP2. Generally speaking, the hybrid grouper obtained different serum and DI immune responses under different doses of 11S, and these responses were ultimately manifested in growth performance. SB can effectively enhance serum immunity and relieve intestinal inflammation caused by high dose 11S.